Method for constructing high-viscosity super-hydrophobic surface through laser assisted by atomized silicone oil and application

Through the atomized silicone oil-assisted laser construction method, the problem of complex and low efficiency of high adhesion superhydrophobic surface preparation process in the prior art is solved, and efficient and environmentally friendly high adhesion superhydrophobic surface preparation is achieved, which is suitable for a variety of application fields.

CN119681442AActive Publication Date: 2025-03-25SUZHOU UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411585290.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-25
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

When preparing high-adhesive superhydrophobic surfaces, the prior art has complex processes, low efficiency, and is not environmentally friendly. The surface functions obtained are single, and only have superhydrophobicity and no high adhesion.

Method used

The method of constructing a highly viscous superhydrophobic surface with atomized silicone oil assisted laser includes grinding and pretreatment of the sample surface, atomizing silicone oil treatment, laser etching and judging the adhesion and hydrophobicity of the surface.

Benefits of technology

It realizes simple, green, low-cost and efficient high-adhesion superhydrophobic surface preparation, with superhydrophobic and high adhesion properties, and is suitable for droplet transportation, drug delivery and mist collection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681442A_ABST
    Figure CN119681442A_ABST
Patent Text Reader

Abstract

The invention discloses a method for constructing a high-viscosity super-hydrophobic surface by using atomized silicone oil to assist laser and application, and the method comprises the following steps: polishing and cleaning the surface of a sample; silicone oil with specific viscosity, density and surface tension parameters is finely atomized through a minimum quantity lubrication device, parameters such as gas and liquid flow and gas inlet pressure are controlled, and it is ensured that the silicone oil uniformly and fully covers the surface of a sample; setting parameters of a laser, outputting laser, and etching the surface of the sample; a processed sample is cleaned, wettability and adhesiveness tests are conducted on the surface of the sample, the prepared surface has high adhesiveness and super-hydrophobicity, and through the atomized silicone oil technology, the preparation method is easy to operate and implement; the health of operators is not influenced; machining efficiency is high, machining quality is good, and economic benefits are achieved; compared with a traditional super-hydrophobic-super-hydrophilic surface prepared through secondary laser, the prepared high-adhesion super-hydrophobic surface can be applied to liquid conveying, and due to high adhesion, the flow slowing effect is achieved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wettability and adhesive surface preparation, and in particular to a method and application of atomized silicone oil-assisted laser construction of a highly viscous super-hydrophobic surface. Background Art

[0002] Inspired by rose petals and gecko feet, highly adhesive superhydrophobic surfaces have attracted extensive attention from researchers at home and abroad due to their promising applications in lossless droplet manipulation, rapid biological or chemical analysis, and surface tension-driven droplet transport. Although considerable progress has been made in the study of the mechanism of highly adhesive superhydrophobic surfaces, there are still challenges in exploring satisfactory manufacturing techniques. So far, several processes for preparing highly adhesive superhydrophobic surfaces have been established.

[0003] The Korean invention patent with publication number KR20230056232A discloses a method for preparing a super-hydrophobic metal surface, using a selective laser melting type metal 3D printer to form a super-hydrophobic pattern, applying silicone oil treatment on the surface, and finally heat treating to obtain a super-hydrophobic surface. The Chinese invention patent with publication number CN114558764A discloses a method for preparing an efficient super-hydrophobic surface, which uses a laser beam to process a micro-nano structure on the substrate surface, drips a mixed solution of silicone oil and isopropanol on the substrate surface, and finally performs low-temperature heat treatment to prepare a super-hydrophobic surface. These methods use silicone oil to treat the surface and perform heat treatment, and the preparation process is simple, green and efficient, but the surface function obtained is single, only super-hydrophobicity is possessed, and there is no high adhesion.

[0004] The Chinese invention patent with publication number CN114457338A discloses a super-high adhesion super-hydrophobic brass surface, which uses a mixed solution of sodium hydroxide and ammonium persulfate for chemical etching, and after constant high temperature heat treatment for 1h, a low surface energy solution is used to modify the surface, and finally constant temperature drying is performed for 1h to obtain a high adhesion super-hydrophobic surface. The Chinese invention patent with publication number CN113463159A discloses a method for preparing a high wear-resistant rose petal effect titanium alloy surface, which uses micro-arc oxidation and boronization treatment to form a microstructure, and completes low surface energy modification through electrophoretic deposition and fluorination treatment to obtain a high adhesion super-hydrophobic surface. The Korean invention patent with publication number WO2011078625A2 discloses an aluminum surface treatment method for adjusting the adhesion performance of the water droplet surface, and a microstructure is formed by gradually controlling the anodizing technology, and then the surface is modified to make the surface have super-hydrophobicity and adhesion. These methods can prepare a super-hydrophobic surface with high adhesion, and the preparation process is relatively complicated and has high requirements on the professionalism of the operator. In addition, some methods use chemicals that may be harmful to the operator and the environment.

[0005] Therefore, there is an urgent need for a simple, green, low-cost and efficient method to prepare a highly adhesive super-hydrophobic surface. This patent proposes a method for atomized silicone oil-assisted laser construction of a highly adhesive super-hydrophobic surface. Summary of the invention

[0006] In view of the above-mentioned problems of complex process, low processing efficiency and environmental pollution in preparing highly adhesive super-hydrophobic surfaces, a method for constructing highly adhesive super-hydrophobic surfaces by atomized silicone oil-assisted laser is proposed in the present invention.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for constructing a highly viscous super hydrophobic surface by atomized silicone oil assisted laser, which comprises:

[0008] S1: Grinding pretreatment of the sample surface;

[0009] S2: Treat the sample with atomized silicone oil;

[0010] S3: laser etching the sample;

[0011] S4: Determine the adhesion and hydrophobicity of the sample surface.

[0012] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil laser according to the present invention, the polishing pretreatment of the sample surface comprises:

[0013] The surface of the sample with the size of U×W is polished by using ordinary sandpaper of different specifications in turn through the grinding machine;

[0014] Place the sample in a glass dish, pour in anhydrous ethanol, then place the glass dish in an ultrasonic cleaner and set the cleaning time to t1;

[0015] After cleaning, use a drying oven to dry the surface of the sample for time t2.

[0016] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil by laser according to the present invention, the atomized silicone oil treatment of the sample comprises:

[0017] S21: Put the silicone oil with viscosity η, density ρ and surface tension σ into the oil tank of the micro-lubrication device, fix the sample, select a round nozzle with a diameter of A, and adjust the distance between the nozzle and the surface of the sample to L;

[0018] Set the air inlet pressure P of the micro-lubrication device a , liquid flow rate Q1 and air flow rate Q2, and the average diameter D of the atomized droplets is obtained according to the following formula.

[0019]

[0020] Among them, K is the proportionality coefficient and n is the exponential parameter.

[0021] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil by laser according to the present invention, wherein: the atomized silicone oil treatment of the sample further comprises:

[0022] S22: turning on the switch of the micro-lubrication device to perform atomized silicone oil treatment for a time period of t3;

[0023] The spray field was photographed using a high-speed camera, and the contour of the atomized droplets was analyzed using image processing software to obtain the average diameter D of the atomized droplets.

[0024] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil by laser according to the present invention, wherein: the atomized silicone oil treatment of the sample further comprises:

[0025] S23: According to the following formula, the velocity v0 of the atomized droplets ejected from the nozzle, the Weber number We, the Reynolds number Re and the capillary number Ca are obtained to measure the atomization effect;

[0026]

[0027] Among them, Q2 is the air flow rate, A is the nozzle diameter, η is the silicone oil viscosity, ρ is the silicone oil density, σ is the silicone oil surface tension, D is the average diameter of the atomized droplets, V0 is the nozzle spray speed, We is the Weber number, Re is the Reynolds number, and Ca is the capillary number.

[0028] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil by laser according to the present invention, wherein: the atomized silicone oil treatment of the sample further comprises:

[0029] S24: Determine the size of We, Re and Ca according to the calculation results;

[0030] If We≥10, Re≥4000, and Ca≥1, the atomized droplets are easy to break, deform, and spread, forming a thinner liquid film on the surface; otherwise, the atomized droplets are stable and difficult to break, forming a rounded shape on the surface, slowly depositing, and spreading limitedly.

[0031] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface with the aid of atomized silicone oil by laser according to the present invention, the sample is subjected to laser etching, including:

[0032] S31: Turn on the laser switch, set the laser scanning path to a cross shape, draw a grid pattern on the computer controller as a processing pattern, and set the processing pattern size to U×W; and,

[0033] Wherein, the laser scanning speed is set to v, the laser scanning interval is set to d, the number of processing times is set to N, the laser power is set to P, the frequency is set to f, the pulse width is set to τ, and the spot diameter is set to w; and,

[0034] Place the sample in the processing area and click the marking button to perform laser etching to prepare the surface microstructure;

[0035] S32: Use deionized water to rinse the surface of the sample after laser processing to remove most of the silicone oil and residue on the surface, then put the sample into a glass dish, pour in anhydrous ethanol, and then put the glass dish into an ultrasonic cleaning machine, set the cleaning time t4, and after cleaning, use a drying oven to dry the surface of the sample for a time of t2;

[0036] S33: Perform a wettability test on the cleaned sample, and use a contact angle meter to measure the static contact angle θ of the sample surface.

[0037] As a preferred solution of the method for constructing a highly viscous super-hydrophobic surface by laser assisted by atomized silicone oil according to the present invention, wherein: the determination of the adhesion and hydrophobicity of the sample surface includes:

[0038] S41: Determine the size of the static contact angle θ;

[0039] If θ is less than 150°, the operation process of S21 to S33 is repeated, wherein the laser scanning speed v and the laser scanning interval d in S31 are numerically reduced to improve the hydrophobicity;

[0040] If θ ≥ 150°, the surface is tested for adhesion.

[0041] As a preferred solution of the method for constructing a highly viscous super hydrophobic surface with the aid of atomized silicone oil laser according to the present invention, wherein: the determination of the adhesion and hydrophobicity of the sample surface also includes:

[0042] S42: Conduct adhesion test on the sample, measure the contact angle hysteresis on the surface, and measure the two different contact angles formed on both sides of the three-phase contact line, namely the advancing contact angle θ A and the receding contact angle θ R , the difference between the two contact angles is the contact angle hysteresis Δθ;

[0043] S43: Determine the size of the contact angle hysteresis Δθ; and

[0044] If Δθ<30°, the operation process of S21 to S42 is repeated, wherein the viscosity η of the silicone oil in S21 is increased to improve the adhesion; and,

[0045] If Δθ≥30°, the preparation is qualified and the operation is completed.

[0046] One of the beneficial effects of the present invention is that by providing a method for constructing a high-viscosity super-hydrophobic surface by laser assisted by atomized silicone oil, it is only necessary to perform a simple atomized silicone oil pretreatment on the sample surface and then perform laser etching to obtain a high-adhesion super-hydrophobic surface. The operation is simple and easy to implement. The silicone oil used is polydimethylsiloxane, which is a non-toxic and odorless item and has no health impact on the operator. Only a short period of atomized silicone oil treatment is required, and the processing efficiency is high and the processing quality is good, which has economic benefits. Moreover, through the preparation method, the surface can be customized and modified. Compared with the surface prepared by the silicone oil heat treatment method which only has hydrophobicity, by selectively performing laser treatment on the atomized silicone oil surface, a hydrophobic-hydrophilic coexistence surface can be achieved. In addition, compared with the super-hydrophobic-super-hydrophilic surface prepared by the traditional secondary laser, the prepared high-adhesion super-hydrophobic surface can not only be used for liquid transportation, but also, due to its high adhesion, a slow flow effect can be achieved at the same time.

[0047] In view of the use of the above-mentioned sample surface, the application of the method of constructing a highly viscous super-hydrophobic surface by laser assisted by atomized silicone oil in the present invention is proposed.

[0048] To solve the above technical problems, the present invention provides the following technical solutions: an application of a method for constructing a high-viscosity super-hydrophobic surface by laser assisted by atomized silicone oil, which includes implementing a method for constructing a high-viscosity super-hydrophobic surface by laser assisted by atomized silicone oil to obtain a high-adhesion super-hydrophobic surface, which is applied to droplet transportation, drug delivery, and fog collection engineering.

[0049] Another beneficial effect of the present invention:

[0050] 1. High-adhesion super-hydrophobic surfaces can be used to precisely control the transport of droplets. By creating a specific wettability pattern on the surface, the path of the droplets on the surface can be designed to achieve directional movement of the droplets. This property is very useful in microfluidics and lab-on-a-chip technology, and can be used to precisely control the transport of droplets during chemical reactions and biological detection. For example, anisotropic super-hydrophobic surfaces can be used to achieve anisotropic flow of droplets, and by controlling the distribution of surface microstructures, droplet transport in a specific direction can be achieved, which has potential application value in chemical production and research.

[0051] 2. In the field of drug delivery, superhydrophobic surfaces can be used as drug carriers to control the release of drugs through external stimuli (such as ultrasound, temperature changes, etc.). For example, superhydrophobic titanium oxide nanotube arrays can be used as drug reservoirs, and ultrasound can be used as a trigger for drug release to achieve on-demand drug release. This smart responsive surface provides a new platform for drug delivery, which can be used to control protein adsorption and maintain bacterial growth, etc. It can also become a platform for drug delivery devices and diagnostic tools.

[0052] 3. Highly adhesive superhydrophobic surfaces can be applied to fog collection. By simulating the droplet collection mechanism in nature, such as the superslippery surface of pitcher plants, efficient fog water collection materials can be developed. These materials can use their superhydrophobic properties to promote the formation and shedding of droplets, thereby achieving efficient collection of water from fog. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0054] Figure 1 This is a schematic diagram of the process of the method for constructing a highly viscous super-hydrophobic surface by atomized silicone oil-assisted laser in the present invention.

[0055] Figure 2 It is a schematic diagram of the structure of the micro-lubrication device in the present invention.

[0056] Figure 3 A schematic diagram showing the comparison of the atomization effects in the present invention

[0057] Figure 4 Schematic diagram of the laser structure in the present invention.

[0058] Figure 5 Schematic diagram of the laser scanning path in the present invention.

[0059] Figure 6 Schematic diagram of contact angle hysteresis measurement of the high adhesion superhydrophobic surface in the present invention.

[0060] Figure 7 Schematic diagram of static contact angle and contact angle hysteresis of three surfaces in the present invention.

[0061] Figure 8 These are X-ray diffraction analysis images of three surfaces in the present invention.

[0062] Fig. 9 These are X-ray photoelectron spectroscopy analysis images of the three surfaces in the present invention.

[0063] In the figure: 100, sample; 200, micro-lubrication device; 201, oil tank; 202, nozzle; 203, air inlet; 204, pressure gauge; 205, pressure knob; 206, filter copper core; 207, frequency generator; 208, gas diverter; 209, combinable pump; 210, air flow control valve; 211, liquid flow knob; 300, test water drop; 400, laser; 401, computer controller; 402, focusing lens; 403, reflector; 404, laser light source; d, laser scanning interval; w, spot diameter. DETAILED DESCRIPTION

[0064] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0065] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0066] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0067] Secondly, the present invention is described in detail with reference to the schematic diagram. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0068] Example 1

[0069] Reference Figure 1 , which is the first embodiment of the present invention, provides a method for constructing a highly viscous super hydrophobic surface with the assistance of atomized silicone oil laser, the method comprising the following steps S1 to S4:

[0070] S1: Pre-grinding the surface of the sample 100;

[0071] S2: treating the sample 100 with atomized silicone oil;

[0072] S3: performing laser etching on the sample 100;

[0073] S4: Determine the adhesion and hydrophobicity of the surface of the sample 100.

[0074] The sample is preferably a titanium alloy plate. By implementing steps S1 to S4, it can have high adhesion and super hydrophobicity, thereby improving corrosion resistance, enhancing self-cleaning ability, optimizing anti-icing performance and friction resistance, etc., so that it can be widely used in biomedical applications, chemical and petroleum industries and other fields.

[0075] Among them, the atomized silicone oil treatment time is 1 min.

[0076] In summary, through the provided method of constructing a highly viscous super-hydrophobic surface by atomized silicone oil-assisted laser, it is only necessary to pre-treat the sample surface with atomized silicone oil and then perform laser etching. The overall operation method is simple, convenient and easy to implement.

[0077] Example 2

[0078] Reference Figure 1 to Figure 6 , which is the second embodiment of the present invention. This embodiment is based on the previous embodiment, but differs in that specific operation methods are provided in each step S1 to S4.

[0079] In step S1, the specific operations are implemented as follows:

[0080] The surface of the sample 100 with the size of U×W is polished by using ordinary sandpaper of different specifications in turn through the grinding machine to remove the surface oxide layer and obtain a relatively smooth surface;

[0081] Place the sample 100 in a glass dish, add an appropriate amount of anhydrous ethanol until the sample can be completely immersed, then place the glass dish in an ultrasonic cleaner, set the cleaning time to t1, and press the "Start" button to clean and remove the debris on the surface caused by grinding;

[0082] After cleaning, the surface of the sample 100 is dried in a drying oven for a time period of t2.

[0083] After step S1 is completed, step S2 is implemented, and step S2 includes sub-steps S21 to S24 in sequence:

[0084] In S21, the micro-lubrication device 200 is debugged, wherein the micro-lubrication device 200 is a quasi-dry external oil supply device, such as Figure 2 As shown, the micro-lubrication device 200 consists of an oil tank 201, a nozzle 202, an air inlet 203, a pressure gauge 204, a pressure knob 205, a filter copper core 206, a frequency generator 207, a gas diverter 208, a combinable pump 209, an air flow control valve 210, and a liquid flow knob 211; the preset parameters of the micro-lubrication device 200 include air inlet pressure, liquid flow, air flow, nozzle diameter, and nozzle distance.

[0085] Put the silicone oil with viscosity η, density ρ and surface tension σ into the oil tank 201 of the micro-lubrication device 200, ensure that the oil amount is above the "minimum oil amount line", fix the sample 100, select the round nozzle 202 with a diameter of A, and adjust the position of the nozzle 202 so that the distance from the surface of the sample 100 is L;

[0086] Through the relationship between the average diameter of atomized droplets and related parameters, D = f{P a , Q1, Q2, A}, adjust the various parameters of the micro-lubrication device, set the inlet pressure P of the micro-lubrication device 200 a , liquid flow Q1 and air flow Q2, and the intake pressure is controlled to P by observing the pressure gauge 204 and adjusting the pressure knob 205 a , adjust the liquid flow knob 211, set the oil consumption to Q1; adjust the air flow control valve 210, control the air flow Q2, and adjust the appropriate gas-liquid ratio so that the silicone oil is sprayed in a good atomized form.

[0087] According to the experimental data, the empirical formula is obtained, Q2∝P a 0.5 , D∝A, the following formula is summarized to obtain the average diameter D of the atomized droplets.

[0088]

[0089] Among them, K is the proportionality coefficient and n is the exponential parameter.

[0090] In S22, the switch of the micro-lubrication device 200 is turned on to perform atomized silicone oil treatment for a time period of t3;

[0091] Use a high-speed camera to shoot the spray field, decompose the recorded video into single-frame images, import them into the image processing software ImageJ, use the edge detection algorithm to identify the outline of the droplets, calculate the diameter of each droplet, and count the sizes of all droplets. Use the image processing software to perform data analysis on the outline of the atomized droplets and obtain the average diameter D of the atomized droplets.

[0092] In S23, the following formula is calculated by the corresponding mapping formula, v0 = f{Q2, A}, {Wa, Re, Ca} = f{η, ρ, σ, D, v0}, and the velocity v0, Weber number We, Reynolds number Re and capillary number Ca of the atomized droplets ejected from the nozzle 202 are obtained according to the following formula, so as to measure the atomization effect;

[0093]

[0094] Among them, Q2 is the air flow rate, A is the nozzle diameter, η is the silicone oil viscosity, ρ is the silicone oil density, σ is the silicone oil surface tension, D is the average diameter of the atomized droplets, V0 is the nozzle spray speed, We is the Weber number, Re is the Reynolds number, and Ca is the capillary number.

[0095] In S24, the magnitudes of We, Re and Ca are determined according to the calculation results;

[0096] If We≥10, Re≥4000, and Ca≥1, the atomized droplets are easy to break, deform, and spread, forming a thin liquid film on the surface, such as Figure 3 As shown on the left; on the contrary, the atomized droplets are stable and difficult to break, the atomization effect is poor, a rounded shape is formed on the surface, the deposition is slow, and the spreading is limited, such as Figure 3 Shown on the right.

[0097] In S31, a laser 400 is used. The laser 400 is selected as an ultraviolet nanosecond pulse laser, which is composed of a computer controller 401, a focusing lens 402, a reflector 403, and a laser light source 404. The preset parameters of the laser include laser scanning speed, laser scanning spacing, laser processing area, laser power, frequency, pulse width and spot diameter, such as Figure 5 As shown, d is the laser scanning distance, w is the spot diameter, the laser 400 is turned on, and the program value can be preset through the computer controller 401;

[0098] Turn on the switch of the laser 400, set the laser scanning path to a cross shape, draw a grid pattern on the computer controller 401 as a processing pattern, and set the processing pattern size to U×W; and,

[0099] Wherein, the laser scanning speed is set to v, the laser scanning interval is set to d, the number of processing times is set to N, the laser power is set to P, the frequency is set to f, the pulse width is set to τ, and the spot diameter is set to w; and,

[0100] Place the sample 100 in the processing area, click the marking button for laser etching, the laser light source 404 outputs laser, and the laser is focused on the sample 100 through the reflector 403 and the focusing lens 402 for etching to prepare a surface microstructure.

[0101] In S32, the surface of the sample 100 after laser processing is rinsed with deionized water to remove most of the silicone oil, black matter generated by the silicone oil after laser processing, and chips generated by the sample 100 after laser processing. Then, the sample 100 is placed in a glass dish, anhydrous ethanol is poured into it, and then the glass dish is placed in an ultrasonic cleaning machine, that is, the sample 100 is placed in the ultrasonic cleaning machine and anhydrous ethanol is used as a solvent for cleaning. The cleaning time t4 is set, and the "start" button is pressed to clean. After cleaning, the surface of the sample 100 is dried in a drying oven for a time of t2.

[0102] Among them, the cleaning method is deionized water, ultrasonic wave, anhydrous ethanol and fine brush cleaning;

[0103] In S33, the wettability test is performed on the cleaned sample 100. The sample 100 is placed on a test platform. As the platform rises, the surface gradually approaches the droplet 300. After contact, it is squeezed to make full contact. Then, the platform is lowered to separate the droplet 300 from the syringe. The static contact angle θ of the surface of the sample 100 is measured using a contact angle meter.

[0104] After step S3 is completed, step S4 is implemented, and step S4 includes sub-steps S41 to S43 in sequence:

[0105] In S41, the size of the static contact angle θ is determined;

[0106] If θ is less than 150°, the operation process of S21 to S33 is repeated, wherein the hydrophobicity is improved by reducing the laser scanning speed v and the laser scanning spacing d in S31, that is, assuming that the laser scanning speed is 100 mm / s and the laser scanning spacing d is 300 μm before, and the experiment is repeated under the condition of θ less than 150°, the laser scanning speed needs to be reduced to less than 100 mm / s, and the laser scanning spacing d needs to be reduced to less than 300 μm;

[0107] If θ ≥ 150°, the surface is tested for adhesion.

[0108] In S42, the adhesion test of the sample 100 is performed to measure the contact angle hysteresis of the surface. The sample 100 is placed on the test platform. As the platform rises, the surface gradually approaches the droplet 300. After contact, it continues to be squeezed to make it fully contacted. Then, the platform is moved horizontally at a certain speed to make the bottom of the droplet 300 move continuously on the surface. Two different contact angles are formed on both sides of the three-phase contact line, which are the advancing contact angle θ and the advancing contact angle θ. A and the receding contact angle θ R , the difference between the two contact angles is the contact angle hysteresis Δθ;

[0109] The contact angle hysteresis Δθ can indicate the difficulty of the liquid droplet 300 moving on the surface. The larger the value, the more difficult it is for the liquid droplet 300 to move, and also the stronger the adhesion of the surface.

[0110] In S43, the size of the contact angle hysteresis Δθ is determined; and,

[0111] If Δθ<30°, the operation process of S21 to S42 is repeated, wherein the viscosity η of the silicone oil in S21 is increased to improve the adhesion; and,

[0112] If Δθ≥30°, the preparation is qualified and the operation is completed.

[0113] Example 3

[0114] Reference Figures 1 to 9 , which is the third embodiment of the present invention, is based on the previous embodiment, and the difference is that an embodiment for executing the method disclosed in the present invention is provided.

[0115] The sample 100 is Ti6Al4V alloy, the industrial grade is TC4, and the titanium alloy sample with a size of 30×30 mm and a thickness of 4 mm is selected. The specific operation is as follows:

[0116] Z1: Use 600#, 1000#, and 1500# ordinary sandpaper to grind the surface of a titanium alloy plate with a size of 30×30mm and a thickness of 4mm through a grinding machine to remove the surface oxide layer and obtain a relatively smooth surface;

[0117] Place the titanium alloy plate in a glass dish and pour in an appropriate amount of anhydrous ethanol until the titanium alloy plate is completely immersed;

[0118] Place the glass dish in an ultrasonic cleaner for 3 minutes to remove the debris from the surface caused by grinding;

[0119] After cleaning, the surface of the titanium alloy plate was dried in a drying oven for 1 min.

[0120] Z2: Debugging the micro-lubrication device 200. In order to facilitate atomization, form small and uniform droplets, and provide excellent stability, this embodiment uses a viscosity of 20 cSt and a density of 0.95 g / cm 3 and polydimethylsiloxane with a surface tension of 21 mN / m are loaded into the oil tank 201 of the FS type quasi-dry external oil supply device, i.e., the micro-lubrication device 200, produced by Fuji BC Technology Co., Ltd., to ensure that the amount of oil is above the "minimum oil amount line";

[0121] According to the empirical formula Where K = 1.15, n = 0.5, control the relevant parameters to adjust the average diameter of the atomized droplets;

[0122] By observing the pressure gauge 204 and adjusting the pressure knob 205, the intake pressure is controlled within the range of 0.4MPa-0.6MPa, and the liquid flow knob 211 is adjusted to set the oil consumption to 4-8ml / min; the air flow control valve 210 is adjusted to control the air flow to 40-50L / min, so that the average diameter of the atomized droplets sprayed from the nozzle 202 is within the range of 40-80μm;

[0123] The titanium alloy plate was fixed, a round nozzle 202 with a diameter of 3.2 mm was selected, and the position of the nozzle 202 of the micro-lubrication device 200 was adjusted so that it was 30 mm away from the surface of the titanium alloy plate.

[0124] Z3: Turn on the switch of the micro-lubrication device 200, perform atomized silicone oil treatment for 1 min, and use a high-speed camera to shoot the spray field at the same time. Decompose the recorded video into single-frame images, import them into the image processing software ImageJ, use the edge detection algorithm to identify the droplet contour, calculate the diameter of each droplet, count the sizes of all droplets, perform data analysis, and obtain the average diameter of the atomized droplets in the range of 40-80 μm;

[0125] Z4: Calculate the velocity v0, Weber number We, Reynolds number Re and capillary number Ca through the mapping formula, v0 = f{Q2, A}, {Wa, Re, Ca} = f{η, ρ, σ, D, v0};

[0126] The calculation results of the atomized silicone oil in this embodiment are: Weber number ranges from 12,700 to 18,800, Reynolds number ranges from 165,700 to 207,300, and capillary number ranges from 74.9 to 93.7. This indicates that the flow, rupture and deformation behaviors of the droplets during the atomization process are very significant, and a thin liquid film can be formed under the surface.

[0127]

[0128] Z5: Turn on the SJ-ZW05 ultraviolet nanosecond pulse laser and preset the program value through the computer controller 401;

[0129] Set the scanning path to a cross shape; draw a grid pattern as the processing pattern for this time, and set the size of the grid pattern to 30×30, in mm;

[0130] Set the laser scanning speed to 50 mm / s, the laser scanning interval d to 100 μm, the number of processing times to 1, the laser power to 5 W, the frequency to 30 KHz, the pulse width to 30 μs, and the spot diameter w to 50 μm;

[0131] Place the titanium alloy plate in the processing area, click the marking button for laser etching, and the laser light source 404 outputs the laser to focus the laser on the titanium alloy plate through the reflector 403 and the focusing lens 402 for etching to prepare the surface microstructure.

[0132] Z6: Use deionized water to clean most of the silicone oil on the surface of the laser-processed titanium alloy plate, the black matter produced by the laser processing of the silicone oil, and the chips produced by the laser processing of the titanium alloy plate;

[0133] Place the titanium alloy plate in an ultrasonic cleaning machine and use anhydrous ethanol as a solvent to clean for 5 minutes, generally 5-10 minutes, and use a clean fine brush to remove the residual silicone oil on the surface of the titanium alloy plate, the black matter produced by the laser processing of the silicone oil, and the chips produced by the laser processing of the titanium alloy plate;

[0134] After cleaning, the surface of the titanium alloy plate was dried in a drying oven for 1 min.

[0135] Z7: wettability test of the cleaned titanium alloy plate was performed. The titanium alloy plate was placed on the test platform, and a 5 μl water droplet was obtained by squeezing the syringe. The surface gradually approached the droplet 300 as the platform rose;

[0136] After contact, the plate was squeezed for 0.2 mm to ensure full contact, and then the platform was lowered to separate the droplet 300 from the syringe. The surface contact angle of the titanium alloy plate was measured using an SDC-100 contact angle meter, and the static contact angle θ of the surface was found to be 154.0°.

[0137] Z8: Adhesion test on titanium alloy plate to measure the contact angle hysteresis of the surface;

[0138] Place the titanium alloy plate on the test platform, squeeze the syringe to get a 5μl water droplet, and the surface will gradually approach the droplet 300 as the platform rises;

[0139] After contact, continue to squeeze 0.2mm to make it fully contact, then move the platform horizontally at a speed of 5mm / s to make the bottom of the droplet 300 move continuously on the surface, and measure the two different contact angles formed on both sides of the three-phase contact line, which are the advancing contact angle θ A and the receding contact angle θ R , the difference between the two contact angles, i.e. the contact angle hysteresis Δθ is 65.3°;

[0140] The contact angle hysteresis Δθ is greater than 30°, indicating that the surface has high adhesion.

[0141] Z9: Different methods are used to prepare the surface:

[0142] The first method is to directly perform laser etching; after cleaning the surface, its wettability and adhesion are tested. The static contact angle θ of the surface prepared by this method is 0, which has super hydrophilicity and high adhesion.

[0143] The second method is to immerse the titanium alloy plate in a glass dish filled with silicone oil after laser etching, and perform heat treatment at a temperature of 150°C for 20 minutes. After cleaning the surface, its wettability and adhesion are tested. The static contact angle θ of the surface prepared by this method is 154.6°, and the surface is superhydrophobic. The contact angle hysteresis Δθ of the titanium alloy plate surface is measured to be 7.1°.

[0144] The contact angle hysteresis Δθ is less than 30°, and the surface does not have high adhesion.

[0145] The surface prepared using the method of this application has a surface contact angle of 154.0° and a contact angle hysteresis Δθ of 65.3°. The surface is both superhydrophobic and highly adhesive.

[0146] Z10: X-ray diffraction analysis - XRD - of three surfaces;

[0147] Depend on Figure 7 It can be seen that the surface processed directly by laser and the surface treated by silicone oil heat show hydrophilic titanium oxide and titanium, while the surface treated by atomized silicone oil shows only titanium;

[0148] The absence of hydrophilic titanium oxide on the surface is one of the reasons why the surface prepared by the present invention has super hydrophobicity.

[0149] Z11: X-ray photoelectron spectroscopy analysis - XPS - of three surfaces;

[0150] Depend on Fig. 9 a It can be seen that the C1s peak and Si2p peak of the surface treated with atomized silicone oil are significantly higher than those of the surface directly processed by laser and the surface treated with silicone oil; the Ti2p peak is significantly lower than the Ti2p peaks of the other two surfaces;

[0151] Further analysis, by Fig. 9 b It can be seen that the CC group content of the surface directly processed by laser is 73.90%, the CC group content of the surface treated by silicone oil heat treatment reaches 81.49%, and the non-polar CC group content of the surface treated by atomized silicone oil reaches 92.73%; CC group is a non-polar group, the lower the surface polarity, the stronger the hydrophobicity; the high CC group content on the surface is one of the reasons why the surface prepared by the present invention has super hydrophobicity;

[0152] Depend on Fig. 9 c shows that the surface O treated with atomized silicone oil 2- The content of metal oxide groups is much lower than that of the other two surfaces. 2- The group content is only 3.40%, which further proves that the surface treated with atomized silicone oil has no hydrophilic titanium oxide;

[0153] And, by Fig. 9 c It can be seen that the SiO2 content of the surface treated with atomized silicone oil is 20.56%, the content of the surface directly processed by laser and the surface treated with silicone oil are 3.29% and 0, respectively; SiO2 can form a strong interaction with polar molecules (such as water), which enhances the adhesion of the surface treated with atomized silicone oil.

[0154] Example 4

[0155] Reference Figures 1 to 9 , which is the fourth embodiment of the present invention, and this embodiment proposes an application of a method for constructing a high-viscosity super-hydrophobic surface by laser assisted by atomized silicone oil.

[0156] Specifically, by implementing the proposed method of atomized silicone oil-assisted laser construction of a high-adhesion super-hydrophobic surface, a high-adhesion super-hydrophobic surface can be obtained, which can be applied to the fields of droplet transport, drug delivery, and fog collection engineering.

[0157] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, as well as parameter values, mounting arrangements, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of performing the function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0158] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.

[0159] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.

[0160] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for constructing a highly viscous super-hydrophobic surface by laser assisted by atomized silicone oil, characterized in that: include, S1: Pre-treating the surface of the sample (100) by grinding; S2: treating the sample (100) with atomized silicone oil; S3: performing laser etching on the sample (100); S4: Determine the adhesion and hydrophobicity of the surface of the sample (100).

2. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 1, characterized in that: The grinding pretreatment of the surface of the sample (100) comprises: The surface of the sample (100) with a size of U×W is polished by using ordinary sandpaper of different specifications in turn through a grinding machine; Place the sample (100) in a glass dish, pour in anhydrous ethanol, and then place the glass dish in an ultrasonic cleaning machine, setting the cleaning time to t1; After cleaning, the surface of the sample (100) is dried in a drying oven for a time period of t2.

3. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 2, characterized in that: The atomized silicone oil treatment of the sample (100) comprises: S21: Silicone oil with a viscosity of η, a density of ρ and a surface tension of σ is loaded into the oil tank (201) of the micro-lubrication device (200), the sample (100) is fixed, a round nozzle (202) with a diameter of A is selected, and the distance between the nozzle (202) and the surface of the sample (100) is adjusted to L; Setting the air inlet pressure P of the micro-lubrication device (200) a , liquid flow rate Q1 and air flow rate Q2, according to the following formula, the average diameter D of the atomized droplets is obtained; Among them, K is the proportionality coefficient and n is the exponential parameter.

4. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 3, characterized in that: The atomized silicone oil treatment of the sample (100) further comprises: S22: turning on the switch of the micro-lubrication device (200) to perform atomized silicone oil treatment for a time period of t3; The spray field was photographed using a high-speed camera, and the contour of the atomized droplets was analyzed using image processing software to obtain the average diameter D of the atomized droplets.

5. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 4, characterized in that: The atomized silicone oil treatment of the sample (100) further comprises: S23: According to the following formula, the velocity v0 of the atomized droplets ejected from the nozzle (202), the Weber number We, the Reynolds number Re and the capillary number Ca are obtained, thereby measuring the atomization effect; Among them, Q2 is the air flow rate, A is the nozzle diameter, η is the silicone oil viscosity, ρ is the silicone oil density, σ is the silicone oil surface tension, D is the average diameter of the atomized droplets, V0 is the nozzle spray speed, We is the Weber number, Re is the Reynolds number, and Ca is the capillary number.

6. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 5, characterized in that: The atomized silicone oil treatment of the sample (100) further comprises: S24: Determine the size of We, Re and Ca according to the calculation results; If We≥10, Re≥4000, and Ca≥1, the atomized droplets are easy to break, deform, and spread, forming a thinner liquid film on the surface; otherwise, the atomized droplets are stable and difficult to break, forming a rounded shape on the surface, slowly depositing, and spreading limitedly.

7. The method for constructing a highly viscous super-hydrophobic surface by laser assisted by atomized silicone oil as described in claims 1 to 6, characterized in that: The sample (100) is laser etched, comprising: S31: Turn on the switch of the laser (400), set the laser scanning path to a cross shape, draw a grid pattern on the computer controller (401) as a processing pattern, and set the processing pattern size to U×W; and, Wherein, the laser scanning speed is set to v, the laser scanning interval is set to d, the number of processing times is set to N, the laser power is set to P, the frequency is set to f, the pulse width is set to τ, and the spot diameter is set to w; and, Place the sample (100) in the processing area, click the marking button to perform laser etching, and prepare the surface microstructure; S32: using deionized water to rinse the surface of the sample (100) after laser processing to remove most of the silicone oil and residue on the surface, then placing the sample (100) in a glass dish, pouring anhydrous ethanol into it, and then placing the glass dish in an ultrasonic cleaning machine, setting the cleaning time t4, and after cleaning, using a drying oven to dry the surface of the sample (100) for a time of t2; S33: Perform a wettability test on the cleaned sample (100), and use a contact angle meter to measure the static contact angle θ of the surface of the sample (100).

8. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 7, characterized in that: The step of determining the adhesion and hydrophobicity of the surface of the sample (100) comprises: S41: Determine the size of the static contact angle θ; If θ is less than 150°, the operation process of S21 to S33 is repeated, wherein the laser scanning speed v and the laser scanning interval d in S31 are numerically reduced to improve the hydrophobicity; If θ ≥ 150°, the surface is tested for adhesion.

9. The method for constructing a highly viscous super-hydrophobic surface by laser assisted atomized silicone oil as claimed in claim 8, characterized in that: The step of determining the adhesion and hydrophobicity of the surface of the sample (100) further includes: S42: Conduct an adhesion test on the sample (100) to measure the contact angle hysteresis of the surface, and measure two different contact angles formed on both sides of the three-phase contact line, namely, advancing contact angle θ A and the receding contact angle θ R , the difference between the two contact angles is the contact angle hysteresis Δθ; S43: Determine the size of the contact angle hysteresis Δθ; and If Δθ<30°, repeat the operation process of S21 to S42, wherein the viscosity η of the silicone oil in S21 is increased to improve the adhesion; and If Δθ≥30°, the preparation is qualified and the operation is completed.

10. An application of a method for constructing a highly viscous super-hydrophobic surface by laser assisted by atomized silicone oil, characterized in that: The method for constructing a highly adhesive super-hydrophobic surface by laser assisted by atomized silicone oil as described in claim 1 is implemented to obtain a highly adhesive super-hydrophobic surface, which is applied to droplet transport, drug delivery, and fog collection engineering.

Citation Information

Patent Citations

  • Preparation method of high-abrasion-resistant titanium alloy surface with rose petal effect

    CN113463159A

  • Preparation method and application of ultrahigh-adhesiveness super-hydrophobic brass surface

    CN114457338A

  • Aluminum surface treatment method capable of adjusting the surface adhesion characteristics of water drops

    WO2011078625A2

  • Method for preparing aluminum alloy super-hydrophobic functional surface by laser marking machine

    CN106400022A

  • Method for rapidly preparing titanium alloy bionic super-hydrophobic surface through femtosecond laser

    CN113210872A